PENGARUH SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP KUALITAS PELAYANAN PADA SATUAN KERJA PERANGKAT DAERAH (Survey Pada Pemerintah Daerah Kabupaten Banggai) - Tadeko, Nuryani (Katalogis, 2017)
The research intends to identify and analyze the influence of government internal controlling system that include controlling enviroment, risk assessment, controlling activities, information and communications, and monitoring of service qualities. Primary data was collected through questionnaire and analyzed by multiple linear regressions, simultaneous and partial tests. The test result show that 1) government internal controlling system simultaneously have significant influence on service quality, 2) controlling environment has a positive but insignificant influence on service quality, 3) risk assessment has negative and insignificant influence of service quality, 4) controlling activities have positive and significant inluence of service quality, 5) information and communication have positive and significant influence of service quality, 6) monitoring has negative and insignificant inluence of service quality. The variable that has dominant influence on the service quality is information and communication.